Transformative Tourism Breakthrough in Post Pandemic: An Enigma or Eclipse - Kristianus Oktriono (Bina Nusantara University, 2021)
The development of tourism in Indonesia had entered a critical period, especially during the uncertain COVID-19 pandemic, which affected the tourism industry both economically and socio-culturally. Workers and stakeholders suffered as the multiplier effect of the COVID-19 outbreak. As preparation for dealing with these conditions, the tourism industry strove to adapt with a transformative business model for its sustainability. In this context, the research proposed a transformative business model for the tourism industry so that stakeholders had an adaptive and innovative frame of mind post-pandemic. The model pinpointed on personalization, closed loop, asset sharing, usage-based pricing, collaborative ecosystem, and agility as the key features. This qualitative research used case study that aimed to explore major aspects of an inspirational business model from various industries that had survived over the decades. The results describe applicable business patterns as a contribution to the tourism industry. It is suggested that tourism stakeholders focus more on developing innovative business strategies postpandemic.